RESEARCH ON AUTOMOBILE ACTIVE ROLL CONTROL BASED ON ACTIVE SUSPENSION - YAO JiaLing; WANG Meng; LI ZhiHong; REN Shan; SUN Ning (Jixie qiangdu)
The rolling control of car focus usually on reducing the roll angle passively. This control has the limited performance for increasing handing stability,passing speed,ride comfort and preventing rollover when the car is turning. This project proposes a control methodology to control the automobile to roll toward the turning direction by using the active suspension. A 6-DOF vehicle model with a 2-DOF steering model and a 4-DOF roll model is established. The active roll sliding mode controller which makes the steady-state roll angle error be zero is established after the desired roll angle is established by dynamic analysis. The simulation results confirm the effectiveness of the control method. The controller makes the perceived lateral acceleration and the lateral load transfer rate be greatly reduced,which effectively improves the handling stability,ride comfort,and the vehicle speed when vehicle is turning,and makes the possibility of rollover be decreased extremely.